Study of Lipase Producing Bacterial Strains from Oil Contaminated Soil (Journal of Basic and Applied Research in Biomedicine, 2022)
Lipase producing bacterial strains were isolated from oil contaminated soils and grown on nutrient agar medium containing 1% (w/v) Tween-20. The isolate showing maximum activity was identified by following Berger’s manual. Three bacterial strains such as Bacillus sp., Staphylococcus sp. and Clostridium sp. were isolated from oil contaminated soil sample. Different media parameters were optimized for maximal enzyme production. Peak lipase activity was observed glucose as carbon source, peptone as nitrogen source, at pH 7.0 and temperature at 40°C.